2011
DOI: 10.1103/physrevb.84.174108
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of phase stability of stoichiometric vanadium nitrides

Abstract: First-principles pseudo-potential total-energy and phonon spectrum calculations of various phases of stoichiometric vanadium nitrides with a small number of vanadium and nitrogen vacancies, as well with small carbon and oxygen admixtures were carried out. It was found that the stoichiometric hexagonal and tetragonal vanadium nitrides (VN) were dynamically stable. The NaCl-type VN exhibited lattice instability. The total energy for the computed ground-state phases of VN increased in the sequence: hexagonal (WC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
5
19
0
Order By: Relevance
“…In particular, the PDOS of TaN 0.83 coincides with the results of θ-TaN structure, as highlighted in the inset of figure 1. We observed that these data are similar with those obtained for the first-principles study of phase stability of hexagonal and cubic structures of VN and NbN [26,27]. Compared with the acoustic branch, the optical phonon frequencies change very slightly and can be neglected.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In particular, the PDOS of TaN 0.83 coincides with the results of θ-TaN structure, as highlighted in the inset of figure 1. We observed that these data are similar with those obtained for the first-principles study of phase stability of hexagonal and cubic structures of VN and NbN [26,27]. Compared with the acoustic branch, the optical phonon frequencies change very slightly and can be neglected.…”
Section: Resultssupporting
confidence: 85%
“…A relatively small vacancy concentration stabilized the cubic WN phase and induced the mechanical stability transition from the NaCl phase to the NbO phase [24]. Ivashchenko et al verified that an increase in nitrogen vacancies can increase the frequency of soft mode and induce the stabilization of VN x and NbN x lattice structures [25][26][27][28][29][30][31]. In addition, the θ-TaN structure was stable at 1773-2073 K, while θ-TaN 0.8-0.9 materials have been obtained at a lower temperature (773-2073 K) due to improved nonmetal vacancy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our measured ρ o value, we establish an upper limit, f vac < 0.005, to the vacancy fraction in our VN layers which is an order of magnitude smaller than the value f vac ∼ 0.06 predicted in Ref. [8] to influence the structural stability of VN. Thus, VN has the NaCl structure at room temperature despite having a much lower vacancy concentration.…”
Section: Vn Temperature-dependent Resistivitymentioning
confidence: 99%
“…Three decades ago, Kubel et al [7] reported a cubic-totetragonal phase transition upon cooling bulk polycrystalline stoichiometric VN samples below 204 K. Lattice symmetry breaking was observed by x-ray diffraction and confirmed by heat capacity measurements. Recently, Ivashchenko et al [8] found, using density-functional perturbation theory, that the low-temperature tetragonal-VN structure is dynamically stable at 0 K, with all phonon modes exhibiting positive, real energies.…”
Section: Introductionmentioning
confidence: 99%
“…The results are compared with those obtained using the first-principles calculations.a Reference[25]. b Reference[20]. c Reference[41].…”
mentioning
confidence: 97%